Consideraciones sobre el paradigma de la complejidad dentro de la investigación en las Ciencias Sociales - Prince Torres, Ángel Carmelo (2023)
The complexity paradigm represents a new way of thinking about the construction of knowledge, and that is why in this essay its insertion within the research processes in the social sciences was analyzed. Because of this, the general purpose of the text was to understand certain considerations about the complexity paradigm within social science research. For this purpose, a documentary and qualitative study was carried out, assuming hermeneutics and critical analysis to obtain the final product. As a result, it could be reasoned that the paradigm of complexity represents an overcoming of the positivist paradigm, and represents a less traditional way of researching within the social sciences. It was concluded that research in the social sciences within the framework of complexity, leads to the execution of knowledge production through the study of social reality as a system where the whole and the parts must be taken into account, without the need for a model that guarantees absolute or infallible truths.